Applying Behavioral Science to Agile Practice Evolution. Issue 3 (6th October 2021) - Rosser, Larri; Ganus, Brian
ABSTRACT: Early agile practices developed by trial and error and are retained "because they work." The fact that certain approaches work well in agile realization of products and services is not accidental – it is rooted in the study of psychology, sociology, and human performance. For example, the "ideal agile team size" of 7 plus or minus 2 not only works but is supported by psycho‐social theories such as the Ringleman effect, social channel capacity and short‐term memory limitations. Examples of similar relations between behavioral science and agile patterns abound – preferred planning horizons, methods of estimating effort and approaches to scaling agile all relate to our understanding of human behavior individually and in groups. This article will explore such relationships with the intent to provide agile practitioners with information about the underpinning of practices, and social scientists with examples of how their work contributes to the improvement of agile practices.